Interaction Of Threonine Amino Acid In Aqueous Dimethyl Sulfoxide Solutions At Various Temperatures (Journal of the College of Basic Education, 2023)
Apparent molal volume ɸv, apparent molal volumes at infinite dilution ɸov ,the slope Sv and viscosity B and D coefficients for Threonine (Thr) in (2-10)% w/w aqueous Dimethyl Sulfoxide (DMSO) solvents have been calculated respectively from the density and viscosity measurements at different temperatures 298.15,303.15,308.15and 313.15 K. The results are discussed in the light of solute-solvent and solute-solute interaction, and shows that Threonine behave as structure-breaker in aqueous DMSO solvent.